The Impact of Instructional Supervision Practices on Students’ Academic Performance in Uganda Certificate of Education Examinations in Kamwenge District - Herbert, Nzaana (Kabale University, 2020)
This study investigated the impact of instructional supervision practices on students’ academic performance in Uganda Certificate of Education examinations in selected secondary schools in Kamwenge District. Specific objectives included: to examine the frequency of instructional supervision, to determine the level of students’ performance in Uganda Certificate of Education (UCE) examinations and to establish the relationship between instructional supervision and students performance in Uganda Certificate Education (UCE) examinations in selected secondary schools in Kamwenge district. A total of 277 respondents were sampled from ten selected schools in Kamwenge district and included: teachers, deputy head teachers, head teachers and the District Inspector of schools. Data analysis was done using both Quantitative and qualitative methods. The major findings revealed that the most common forms of supervision in Kamwenge include checking schemes of work, checking teachers’ record of work covered, maintenance of attendance registers and classroom visitation. The research further identified other supervision practices such as staff appraisal and checking lesson plans. The study revealed that the quality of passing was low with majority of students passing in divisions three, four and nine. The low quality of passing was caused by low participation of parents, enrolment of poor grades at senior one, absenteeism of both teachers and learners and low level of supervision by the school administrators. The study showed that instructional supervision practices had a positive relationship with teaching and learning practices. Major recommendations were: need to develop and build a remedial mechanism into the school system, proper staffing of the Directorate of Education Standards, need for increasing teachers’ motivation, regular evaluation of the instructional process, school administration procedure and educational outcomes by the supervisors, need for government to always provide instructional materials and other learning facilities and need to promote capacity development of teachers through intensive and regular seminars/workshops.